Pengaruh Pelilinan dan Suhu Penyimpanan Terhadap Sifat Fisik-Kimia Mentimun (Cucumis sativus L.) - Nurmahari Nurmahari; Syawaluddin Syawaluddin; Imelda Sari Harahap (Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2018)
This study aims to determine the effect of storage room temperature and concentration of beeswax emulsions based on the physical-chemical properties of cucumbers (Cucumis sativus L.). The study used two factorial Complete Randomized Design (CRD) with each treatment four levels of treatment; each treatment was given two replications. The treatment at level 1 consisted of storage temperature (control, 25oC, 27oC, 30oC), the second level consisted of emulsion concentration (control, 6%, 12%, 30%). The parameters observed were texture, weight, moisture content, color, and shelf life. The results showed the interaction of storage room temperature and beeswax emulsion concentrations on cucumber texture, weight, water content showed no significant effect. The longest shelf life interaction is 12 days, while the shortest shelf life in six days. Keywords: Storage, Coiling, Cucumber Temperature